ANALYZING THE PORTRAYAL OF PATRIARCHAL OPPRESSION TOWARDS THE FEMALE CHARACTERS IN J.K. ROWLING’S THE CASUAL VACANCY: A REFLECTIVE POST-FEMINIST CRITICS - Fitri, Nurliana; Suparti, Erni (Fakultas Ilmu Budaya, Universitas Mulawarman, 2016)
The oppression and subordination towards woman mostly happened because of the patriarchal system which exists in the society. The purposes of this study are to analyze the portrayal of patriarchal symbols in the society of Pagford Town in J.K. Rowling’s The Casual Vacancy and the patriarchal system abuse or oppression towards the female characters in J.K. Rowling’s The Casual Vacancy. The results of the study show six symbols of patriarchy which is found in the novel. They are female as sex objects in public patriarchy, male as villain in public patriarchy, male as villain in private patriarchy, female as the faulty in private patriarchy, female as mother or angel in the house in private patriarchy and female as damsel in distress in private patriarchy. The study also shows the indication of abuse occurred to several female characters. The patriarchy system generated from the participation of the male and female is the main cause of the sustainability of female oppression and subordination in the society.Keywords: patriarchy, symbol, oppression, abuse, victimization, The Casual Vacancy